L'impact du déboisement sur l'azote minéral susceptible d'être absorbé par un taillis de chêne vert (Quercus ilex L) en reconstitution - Merzouki, A; Lossaint, P; Billes, G; Rapp, M (Ann. For. Sci., 1990)
The impact of deforestation on the mineral nitrogen available during restoration of the holm oak (Quercus ilex L) coppice. The impact of deforestation on the biological activity of a mediterranean red soil was studied from January 1984 to April 1986 within a holm oak (Quercus ilex L) stand after clearcut. Part of the study involved the estimation of the amount of nitrogen available for vegetation both in the mature holm oak coppice and in the 1-2-yr-old recovery stand. The study indicates that the new shoots essentially took up nitrate nitrogen; however, the mature site used both nitrate and ammonium nitrogen as nitrogen source. The availability of mineral nitrogen, essentially nitrate, ranged from 47.4 to 118.6 kg·ha -1·yr-1 in the rebuilding site and 25.6 to 63.9 kg·ha-1·yr-1 in the mature stand. At the control site, ammonium nitrogen represented 43% of the total nitrogen available.
Keywords: Deforestation; holm oak coppice; nitrate; nitrogen availability; Quercus ilex L; shoots

Crecimiento longitudinal del alcornoque: segmentos y hojas - Caritat, A; Molinas, M; Oliva, M (SCIENTIA gerundensis, 1988)
This paper is directed to the basic understand of longitudinal growth of the cork-tree Quercus suber L. Branch constitution is analized through the relation of segments and leaves. To duly recognize segments in branches, an apropiate nomenclature is used. Segments length changes from 0,2 to 11,6 cm, with an average of 2,3 cm. Two kind of shoots, long and short shoots, can be distinguished. Segment elongation tend to decrease as succesive periods accumulate. No differences in segments can be related to the period of the year in which they were developed. Leaves show heteroblastic distribution. Leave lamina has an average length of 3,3 cm and is 2,O cm wide. Petiol is very constant with an average of 0,6 cm.
Keywords: branch growth; cork-tree; leaves; Quercus-suber; shoots